(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This text analyzes the strategic and economic significance of the North African region during the First and Second World Wars of the 20th century. It examines the mobilization of the local population into military service by colonial powers (France, Great Britain, Italy) and the allocation of regional resources toward metropolitan industries and frontline requirements. Furthermore, it highlights the establishment of industrial enterprises in the region during the war years and the subsequent impact of these processes on national liberation movements.